Genes Associated with Thoracic Aortic Aneurysm and Dissection: 2019 Update and Clinical Implications - Faggion Vinholo, Thais; Brownstein, Adam J.; Ziganshin, Bulat A.; Zafar, Mohammad A.; Kuivaniemi, Helena; Body, Simon C.; Bale, Allen E.; Elefteriades, John A. (AORTA, 2019)
Thoracic aortic aneurysm is a typically silent disease characterized by a lethal natural history. Since the discovery of the familial nature of thoracic aortic aneurysm and dissection (TAAD) almost 2 decades ago, our understanding of the genetics of this disorder has undergone a transformative amplification. To date, at least 37 TAAD-causing genes have been identified and an estimated 30% of the patients with familial nonsyndromic TAAD harbor a pathogenic mutation in one of these genes. In this review, we present our yearly update summarizing the genes associated with TAAD and the ensuing clinical implications for surgical intervention. Molecular genetics will continue to bolster this burgeoning catalog of culprit genes, enabling the provision of personalized aortic care.
Keywords: genetics; thoracic aortic aneurysm; aortic dissection